Perspektif Ekonomi Islam Terhadap Minat Beli Melalui Online Shop - Andini, Azizah Noer; Korina, Asa Prayarsni; Puspitasari, Novi (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
The purpose of this study is to examine how Muslim buyer behavior in online shopping. The type of research used in this research is descriptive qualitative research with a literature study approach. The literature study approach is an approach by reviewing various journals and books related to the perspective of Islamic economics on buying interest through online shops as a reference source. Buying interest in this online shop is influenced by several factors including the existence of timely reviews, quantity reviews, and valence reviews that make buyers very interested in making online buying and selling transactions. This study assumes that various findings from past research in Muslim-majority countries, such as Saudi Arabia and Malaysia, show a mismatch between online buying and selling with sharia. Muslim shoppers are supposed to behave in moderation where they do not overconsume leading to tabdhir (wastefulness) as well as israf (excess) or shortage leading to bukhl (miserliness) as cited in the Quran and As-Sunnah.